Phase behaviour of butane/bitumen fractions: Experimental and modeling studies. (15th May 2018) - Azinfar, Bahareh; Haddadnia, Ali; Zirrahi, Mohsen; Hassanzadeh, Hassan; Abedi, Jalal
Highlights: Bitumen is fractionated to four cuts and each cut is characterized. Solvent solubility, density, and viscosity of butane/bitumen cuts are measured. Using experimental butane solubilities in cuts, generalized model is developed. Model predicts butane solubility in bitumen independent to experimental solubility. Carbon distribution of bitumen obtained by SimDist is the only input to this model. Abstract: Utilization of butane as a solvent in solvent-aided recovery of bitumen has shown to be promising. In these recovery processes, hot butane or butane and steam mixture is injected into subsurface bitumen reservoirs to dilute the bitumen. Diluted bitumen drains to production well and is produced. The primary steps towards an optimized and successful solvent-aided bitumen recovery method are bitumen characterization and phase behaviour study of solvent/bitumen system. In this work, we develop a generalized equation of state (EoS) to predict the butane solubility in bitumen and heavy oils. Bitumen is fractionated experimentally and the measured data for each fraction is used to tune the EoS. The vacuum distillation is utilized to fractionate bitumen into four cuts. Each bitumen cut is then characterized and the phase behaviour data including solubility, density and viscosity of butane/bitumen cuts are measured at three temperatures of 100, 150, and 186 °C and pressures up to 4 MPa. The proposed generalized thermodynamic model predicts butane solubility in bitumen using results of simulated distillation (SimDist) test to define bitumen components. The developed EoS model is evaluated by comparing the calculated solubility of butane in Athabasca and Cold Lake bitumens with experimental data. The results show that the generalized model is able to predict butane solubility in bitumen without using experimental solubility data to tune the EoS with acceptable accuracy. The density and viscosity of original and butane-saturated bitumen cuts are also correlated. The developed model serves as a substitute for time consuming and expensive solubility measurements. These results find applications in design and optimization of solvent-aided recovery process of bitumen.